The Role of Caregivers and Students in Building an Environmental Culture Based on the Eco-Pesantren Concept at Nurul Hidayah Islamic Boarding School, Probolinggo - Lailatul Chasifah; Khoiriyah Khoiriyah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to explore in depth the role of caregivers and students in building an environmental culture based on the eco-pesantren concept at Nurul Hidayah Islamic Boarding School, Probolinggo. This pesantren is one of the Islamic educational institutions that has begun to integrate environmental awareness values into students’ daily activities. The environmental culture developed includes greening activities, cleanliness management, waste sorting, and the habituation of environmentally friendly behavior through religious approaches and exemplary conduct. This research employs a descriptive qualitative approach with a field study method. Data were collected through in-depth interviews with caregivers, administrators, and students, direct observations of environmental activities, and documentation of various pesantren programs. Data analysis was carried out using the interactive Miles and Huberman model through three stages: data reduction, data display, and conclusion drawing. The findings indicate that caregivers play a central role in instilling ecological values through exemplary behavior, guidance, and spiritual reinforcement. Meanwhile, students actively implement these values through participation in environmental activities. The formation of environmental culture in this pesantren is not only supported by formal regulations but also by social influence, religious values, and a continuous habituation process within pesantren life.